Phylogenetics and comparative morphology of crab spiders (Araneae: Dionycha, Thomisidae) - Benjamin, Suresh P. (Zootaxa, 2011)
The higher-level phylogenetic relationships of crab spiders (Thomisidae) are studied from morphological data. 33 taxa are coded for 74 characters (53 binary and 21 multistate). Several analyses using equal, successive and implied weights were carried out. The most parsimonious tree obtained by analysis with successive and implied weights is put forward as the preferred hypothesis of thomisid relationships (length 222 steps, CI 0.74, RI 0.83). Thomisidae emerge monophyletic in all analyses, supported by four unambiguous synapomorphies. It is now apparent that thomisid taxa have been mostly defined on the basis of plesiomorphic character states. A number of taxonomic changes, including the description of new taxa are proposed and the evolution of diverse behaviors of thomisids is studied in light of the new phylogenetic result. Color change behavior evolved once within the family, but eye arrangement patterns of the median ocular quadrangle, thought to be diagnostic for many genera, evolved as much as 10 times independently. The following new species are described: Borboropactus nyerere sp. nov., Cebrenninus srivijaya sp. nov., Geraesta lehtineni sp. nov. and Geraesta mkwawa sp. nov. The following new generic synonymies are proposed: Bucranium O. P.-Cambridge, 1881 = Aphantochilus O. P.-Cambridge, 1870; Sanmenia Song and Kim, 1992 = Pharta Thorell, 1891 and Cupa Strand, 1906 = Epidius Thorell, 1877. The following species are synonymized: Regillus divergens Hogg, 1914 and Borboropactus hainanus Song, 1993 = Borboropactus bituberculatus Simon, 1884 syn. nov., Epidius ganxiensis (Yin, Peng & Kim, 1999) = Epidius rubropictus Simon, 1909 syn. nov., Geraesta bilobata Simon, 1897 = Geraesta hirta Simon, 1889 syn. nov., Sanmenia kohi Ono, 1995 = Pharta bimaculata Thorell, 1891 syn. nov. and Sanmenia zhengi (Ono & Song, 1986) = Pharta brevipalpus (Simon, 1903) syn. nov. The following new combinations are proposed: Aphantochilus taurifrons (O. P.-Cambridge, 1881) comb. nov., Epidius typicus (Bösenberg & Strand, 1906) comb. nov., Pharta brevipalpus (Simon, 1903) comb. nov., Pharta gongshan (Yang, Zhu and Song, 2006) comb. nov., Pharta nigra (Tang, Griswold & Peng, 2009) comb. nov. and Pharta tengchong (Tang, Griswold & Yin, 2009) comb. nov.